Pengaruh Audit Tenure, Pergantian Manajemen dan Financial Distress Terhadap Auditor Switching pada Perusahaan Properti dan Real Estat - Luh Ketut Berliani Sari Sulaksani; Susanto Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the effect of audit tenure, management changes, and financial distress on auditor switching in property & real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The research employs a descriptive quantitative method using secondary data from audited annual financial statements. Samples were selected using purposive sampling, and data analysis was conducted with SPSS version 25. The findings reveal that audit tenure and management changes do not significantly affect auditor switching. In contrast, financial distress has a significant impact, indicating that financially distressed companies are more likely to change auditors to enhance financial report credibility.